1984
DOI: 10.1182/blood.v64.1.296.bloodjournal641296
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of immature T cell subpopulations in neonatal blood

Abstract: A series of monoclonal antibodies directed against T cell differentiation antigens was used to identify circulating T cells in normal human neonates. Twenty-five cord blood samples, taken after cesarean or vaginal delivery, and 16 venous blood samples from normal adult controls were examined using monoclonal antibodies in an indirect immunofluorescence technique. The percentage of circulating OKT3 positive (pan-T cell) cells was significantly lower in the neonatal blood (52.8%) compared with the adult controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…CD4 þ CD8 þ T cells are present in small amounts (2-3%) in normal individuals [9], and their level occasionally reaches 10% [18,20,21]. Their number is also known to be high in cord blood cells [11,12]. The number of CD4 þ CD8 þ T cells is relatively high in patients with myasthenia gravis [13,14], idiopathic thrombocytopenic purpura [15], multiple sclerosis [16], Behçet's syndrome [17] and infectious mononucleosis [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 þ CD8 þ T cells are present in small amounts (2-3%) in normal individuals [9], and their level occasionally reaches 10% [18,20,21]. Their number is also known to be high in cord blood cells [11,12]. The number of CD4 þ CD8 þ T cells is relatively high in patients with myasthenia gravis [13,14], idiopathic thrombocytopenic purpura [15], multiple sclerosis [16], Behçet's syndrome [17] and infectious mononucleosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of cell surface markers on T cells revealed CD4 þ CD8 ¹ and CD4 ¹ CD8 þ T cells in the peripheral blood, in addition to a small number of CD4 þ CD8 þ and CD4 ¹ CD8 ¹ T cells [9,10]. An abnormal increase in the number of CD4 þ CD8 þ T cells in the peripheral blood is known to occur in cord blood [11,12] and in patients with certain diseases including myasthenia gravis [13,14], idiopathic thrombocytopenic purpura [15], multiple sclerosis [16], Behçet's syndrome [17] and infectious mononucleosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, however, have shown an intermediate stage between Stage II and Stage III in which cells are reactive with OKT3 (acquired at Stage III) and OKT6 stimultaneously (Griffiths- Chu et al 1983). Cireulating T-cells are not reaetive with this antibody in normal adult individuals.…”
Section: Monoclonal Anii-t-cell Antibodiesmentioning
confidence: 99%